Waste and Emission Reduction Through Regional Synergies in the Kwinana Industrial Area (The Australasian Institute of Mining and Metallurgy, 2002)
Industries in the Kwinana area have embarked on a journey of improving the eco-efficiency of Western AustraliaÆs primary heavy industry area. The Kwinana Industrial Area has some unique characteristics that provide both opportunities and barriers. The Kwinana Industries Council and the Chamber of Commerce and Industry are working with the industries to identify a range of projects that can deliver improvements for both environmental and economic æbottom linesÆ, and to progress these projects using internal and external resources. The evolution of the process, its relationship to the ethos of operating companies, and the availability of resources to pursue projects, is an interesting study with lessons for others interested in taking the same course.